Stem cell based therapies for spinal cord injury. Issue 4 (August 2016) - Muheremu, Aikeremujiang; Peng, Jiang; Ao, Qiang
Highlights: Spinal cord injury (SCI) is one of the most severe problems for patients. Treatment of spinal cord injury has always been a challenge for clinical practitioners and scientists. Stem cell transplantation technique has brought new hopes for the treatment of SCI. The possible mechanisms of stem cell based therapies for SCI and some relevant aspects have been reviewed in this paper. Abstract: Treatment of spinal cord injury has always been a challenge for clinical practitioners and scientists. The development in stem cell based therapies has brought new hopes to patients with spinal cord injuries. In the last a few decades, a variety of stem cells have been used to treat spinal cord injury in animal experiments and some clinical trials. However, there are many technical and ethical challenges to overcome before this novel therapeutic method can be widely applied in clinical practice. With further research in pluripotent stem cells and combined application of genetic and tissue engineering techniques, stem cell based therapies are bond to play increasingly important role in the management of spinal cord injuries.